Assessment of Knowledge, Attitude and Practices for Women’s toward Family Planning in Primary Health Care Centers at Al-Amara city/ Iraq - Al Abedi, Ghazwan Abdul hussein; Arar, Aqeel Aziz; Alridh, Mustafa Salim Abdul (International Journal of Psychosocial Rehabilitation, 2020)
Objectives: To assess knowledge, attitude and practices (KAP) related to family planning among women and to find out association with their socio-demographic variables. Methodology: A descriptive study conducted on the random selection of five primary healthcare centers during the period from November 11, 2019 and February 27, 2020. A convenient sampling technique was used to select (270) women attending health care services in the city of Al-Amara. Result: The study showed that women’s knowledge, attitudes and practices regarding family planning were at an moderate level of 58.2%, 67% and 55.1%, respectively. The results indicated a high significant relationship between the awareness, beliefs and practices of women toward family planning with some variables under study at (P<0.000), except number of children, it demonstrated that there was non-significant correlation at (P>0.05). Conclusion: In this study, the knowledge level, attitude, and practices toward family planning were relatively moderate when compared to many studies. Each nurse must teach women about family planning as a whole to increase awareness and maintain health.